Do School Accreditation, Education Budget, and Teacher’s Competence Matter for Graduate’s Quality? - Azhari Azhari; Kamaruddin Kamaruddin; Marzuki Marzuki; Ratna Dewi (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2021)
This study examinedthe effect of school accreditation, education budget, and teacher competence on the quality of high school graduates. The analysis method used was a panel regression through the Fixed Effect Model (FEM) approach, and the data were from 2017-2019. The results showed that school accreditation and education budgets had an effect on the quality of graduates. Also, the implication of this study is that schools need to increase accreditation, as well as the education budget. In terms of teacher competence, the teachers need to improve their competence by taking an active role in organizations, training teacher capacity, and mastery of information technology. Meanwhile, teacher competence has no effect on the quality of graduates in senior secondary schools. Simultaneously, all variables have a significant effect on the graduates quality. The limitation of this study is the data used, regardless of the status of private and public schools. Therefore, studies to compare private and public schools are of particular interest.